Sistem Formula dan Fungsi Sastra Lisan dalam Tradisi Sungkem Tlompak di Dusun Keditan Desa Pogalan Kecamatan Pakis Kabupaten Magelang - Wulandari, Annisa Rizki; Ari Widihastuti, Rahma (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
Keditan Hamlet has a traditional story similar to that of other surrounding villages. Based on the search, the variations of the story are related to each other. This research aims to describe the formula system and function of oral literature contained in the stories of the Sungkem Tlompak Tradition in Keditan Hamlet, Pogalan Village, Pakis District, Magelang Regency. This research is qualitative. Data collection techniques include participant observation, in-depth interviews, and documentation. Data analysis involves data reduction, data presentation, and conclusion. The results of this research were the discovery of word, phrase, and sentence formulas. Apart from that, 6 story points were found which can be used as reminder tools for the Keditan community in remembering the storyline of the legend of the Sungkem Tlompak Tradition. The functions of this legendary story are (1) an educational tool for the younger generation, (2) to increase a sense of group solidarity, (3) providing social sanctions or punishments so that people behave well, (4) as a form of social criticism, (5) strengthening and perpetuating traditions, and (6) the Lombok Abang Ijo Warrior Art which is the icon of Keditan Hamlet as a means of entertainment. This research suggests that documentation in the form of video is needed so that the legendary story of the Sungkem Tlompak Tradition can be preserved.